Unsur Dan Faktor Yang Mempengaruhi Pengambilan Keputusan Konsumen - Akbar Ardiansyah; Tsuwaibatul Islamiyah; Nela Budi Eka Sari (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2024)
Decision making is a series of activities carried out by someone in an effortto solve the problems being faced and then determine various alternativesthat are considered the most rational and in accordance with theorganizational environment. So making a decision means choosing andspecifying an alternative that is considered the most profitable of the severalalternatives faced. The stages of a purchase are as follows: (a) problemrecognition, (b) information search, (c) alternative assessment, (d) purchasedecision, (e) post-purchase behavior. Elements of decision making, namely:(a) The purpose of decision making, (b) Identification of alternativedecisions to solve problems, (c) Calculations regarding factors that cannotbe known beforehand or beyond human reach, and (d ) Means or tools toevaluate decision making. Meanwhile, consumer behavior in makingdecisions is influenced by four factors as follows: (a) information factors,(b) education level, (c) social or environmental factors, (d) cultural factors,(e) personal factors, and (f) psychological.